3,4-Diaminopyrazolo[3,4-d]pyrimidines: a new three-component microwave-assisted synthesis and anti-leukemic properties - Ng, Jia Hui; Lim, Felicia Phei Lin; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Royal Society of Chemistry, 2023)
A convenient method for the synthesis of N3,N4-disubstituted 3,4-diaminopyrazolo[3,4-d]pyrimidines was developed using a three-component reaction of 3,5-diaminopyrazole-4-carbonitriles with primary amines and orthoesters. The preparation of 114 examples demonstrated the good scope of the reaction, which tolerated variations in the substrate structure and was particularly efficient under microwave irradiation. The short reaction time and chromatographyfree product isolation add practicality to this method. The anti-leukemic activity was assessed in vitro using K562 and Jurkat T cells, and the selectivity of the most active compounds was 3 evaluated using non-cancerous MRC5 cells. The most promising compound inhibited Jurkat T cells with a GI50 value of 0.5 µM and a selectivity index of 64.